¿Qué es la tierra si ya no la pisamos? Límites entre lo natural y artificial en la ciudad (2024)
Among the forgotten corners of the city, where asphalt, waste, and concrete intertwine like veins of an urban organism, a third landscape emerges. It is not the cared-for garden or the park with wooden benches, but that corner where nature rebels, where plants grow in the cracks of the ground and discarded objects find a final resting place